Methodology for global structural load effect analysis of the semi-submersible hull of floating wind turbines under still water, wind, and wave loads - Wang, Shuaishuai; Moan, Torgeir; Gao, Zhen (Marine structures, 2023)
In designing the support structures of floating wind turbines (FWTs), a key challenge is to determine the load effects (at the cross-sectional load and stress level). This is because FWTs are subjected to complex global, local, static, and dynamic loads in stochastic environmental conditions. Up to now, most of the studies of FWTs have focused on the dynamic motion characteristics of FWTs, while minimal research has touched upon the internal load effects of the support structure. However, a good understanding of the structural load effects is essential since it is the basis for achieving a good design. Motivated by the situation, this study deals with the global load effect analysis for FWT support structures. A semi-submersible hull of a 10-MW FWT is used in the case study. A novel analysis method is employed to obtain the time-domain internal load effects of the floater, which account for the static and dynamic global loads under the still water, wind, and wave loads and associated motions. The investigation of the internal stresses resulting from various global loads under operational and parked conditions and the dynamic behavior of the structural load effects in various environmental conditions are made. The dominating load components for structural responses of the semi-submersible floater and the significant dynamic characteristics under different wind and wave conditions are identified. The dynamic load effects of the floating support structure are investigated by considering the influence of the second-order wave loads, viscous drag loads induced global motions, and wind and wave misalignments. The main results are discussed, and the main findings are summarized. The insights gained provide a basis for improving the design and analysis of FWT support structures. •A novel analysis procedure to obtain the cross-sectional forces, moments, and stresses of the hull using a time-domain approach, is established.•Global structural load effect analysis of a semi-submersible FWT hull is conducted.•Characteristics of the hull internal load effects (forces/moments/stresses) under still water, wind, and wave loads are investigated and differences as compared to those of floater motions are revealed.•Contributions of different sources of loads and different internal forces and moments to the semi-submersible hull stress, are demonstrated.•A significant cancellation effect of different dynamic load sources on the hull stress is identified.